CLIMATE RISK AND FINANCIAL STABILITY: BUILDING RESILIENT FINANCIAL SYSTEMS IN THE FACE OF GLOBAL WARMING - Ari Purwanti; Ming Pong; Rit Som (Journal Markcount Finance, 2026)
Climate change has emerged as a systemic risk with profound implications for global financial stability, affecting asset valuations, credit markets, insurance systems, and macroeconomic resilience. Increasing frequency and severity of climate-related shocks expose financial institutions to physical risks, transition risks, and liability risks that challenge the robustness of existing financial frameworks. This study aims to examine how climate risk interacts with financial stability and to identify strategic approaches for building resilient financial systems in the context of global warming. The research adopts a qualitative analytical design based on an extensive review of secondary data, including peer-reviewed journal articles, policy reports, and regulatory frameworks issued by central banks and international financial institutions. The findings reveal that climate risk amplifies traditional financial vulnerabilities through channels such as asset stranding, credit reallocation, and systemic contagion, while also exposing gaps in risk assessment, disclosure practices, and prudential regulation. Evidence indicates that proactive integration of climate risk into financial supervision, stress testing, and capital allocation enhances systemic resilience and reduces long-term instability. The study concludes that strengthening climate-related financial governance, improving data transparency, and aligning financial incentives with climate objectives are critical for safeguarding financial stability.